(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sulardiono B, Hartoko A, Aini AN, Wulandari D, Budiharjo A. 2021. Genetic diversity of commercial sea cucumbers Stichopus (Echinoderm: Stichopodidae) based on DNA Barcoding in Karimunjawa, Indonesia. Biodiversitas 23: 922-927. DNA barcoding has proven a sufficient tool for species identification in varied groups of marine invertebrates, including crustaceans, mollusks, polychaetes, and echinoderms. The outdated system of morphological identification of the Stichopus spp. group is generally based on color patterns, causing confusion in identification. This study aimed to investigate genetic diversity, confirm the species identification, and examine phylogenetic relationships of the Stichopus genus (Echinoderm: Stichopodae) in the Karimunjawa Sea, by analyzing DNA sequence variation at cytochrome C oxidase subunit I (COI) in mitochondrial DNA and internal transcribed spacers (ITS). This genetic information is very helpful in inventorying and mapping commercial sea cucumber resources in Karimunjawa to support conservation efforts. Three types of sea cucumbers from the genus Stichopus were found, with different local names, namely Crengek gamete, Pace gamete, and Kuning gamete. The results of DNA extraction from the three samples showed that the DNA from soft bone tissue had a better level of purity and concentration than body tissue. The COI phylogenetic tree analysis showed that these samples with different local names were closely related to Stichopus monotuberculatus. Therefore, it is necessary to conserve the resources of the S. monotuberculatus in the management of Karimunjawa sea.